2008
DOI: 10.1017/s0967199407004546
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hyalin and sea urchin gastrulation, Part II: hyalin, an interspecies cell adhesion molecule

Abstract: SummaryThe 330 kDa fibrillar glycoprotein hyalin is a well known component of the sea urchin embryo extracellular hyaline layer. Only recently, the main component of hyalin, the hyalin repeat domain, has been identified in organisms as widely divergent as bacteria and humans using the GenBank database and therefore its possible function has garnered a great deal of interest. In the sea urchin, hyalin serves as an adhesive substrate in the developing embryo and we have recently shown that exogenously added puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Gametes of Lytechinus pictus ( L. pictus ) sea urchins were prepared as described above. Hyalin from S. purpuratus is biologically active with L. pictus (Alvarez et al ., 2008) and antibody to hyalin from one species cross reacts with hyalin from other species (Vater & Jackson, 1990). Eggs collected from individual females were washed separately two times with 100 ml of ASW, pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gametes of Lytechinus pictus ( L. pictus ) sea urchins were prepared as described above. Hyalin from S. purpuratus is biologically active with L. pictus (Alvarez et al ., 2008) and antibody to hyalin from one species cross reacts with hyalin from other species (Vater & Jackson, 1990). Eggs collected from individual females were washed separately two times with 100 ml of ASW, pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…This model is the best organism for studying hyalin function because of the quantity of embryos obtainable and because of the availability and transparency of the sea urchin embryo. Hyalin has been implicated in controlling general adhesive interactions in the sea urchin embryo (Kondo, 1973; Wessel et al ., 1998) and our laboratories provided evidence that hyalin is a cell adhesion molecule involved in mediating specific cellular interactions during the process of archenteron elongation and attachment to the blastocoel roof (Razinia et al ., 2007; Alvarez et al ., 2008; Carroll et al ., 2008; Contreras et al ., 2008), cellular interactions that have interested investigators for over a century (Herbst, 1900).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used two of the assays in identifying a putative role for glucose/mannose groups in the specific adhesive interaction studied here (Latham et al, 1999; Khurrum et al, 2004; Coyle-Thompson & Oppenheimer, 2005; Sajadi et al, 2007) and are currently examining the relationship between these past findings with respect to sugar involvement, and the hyalin results reported here, in Razinia et al (2007), and in Alvarez et al (2007).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular interactions that occur in the sea urchin, recognized by the U.S. National Institutes of Health as a model system, may provide insights into adhesive interactions that occur in human health and disease. In part II of this series, we showed that S. purpuratus hyalin heterospecifically blocked archenteron-ectoderm interaction in Lytechinus pictus embryos (Alvarez et al, 2007). In the current study, we have isolated hyalin from the sea urchin L. pictus and demonstrated that L. pictus hyalin homospecifically blocks archenteron-ectoderm interaction, suggesting a general role for this glycoprotein in mediating a specific set of adhesive interactions.…”
mentioning
confidence: 88%